Direct Electrochemical Reduction of Acetochlor at Carbon and Silver Cathodes in Dimethylformamide. Issue 15 (25th September 2020) - Couto Petro, Ana G.; Thapa, Bishnu; Karty, Jonathan A.; Raghavachari, Krishnan; Baker, Lane A.; Peters, Dennis G.
Abstract : Cyclic voltammetry and controlled-potential (bulk) electrolysis have been employed to investigate the direct electrochemical reduction of acetochlor (1 ) at carbon and silver cathodes in dimethylformamide. Voltammograms of 1 exhibit a single irreversible cathodic peak at both cathode materials. Catalytic properties of silver towards carbon–halogen bond cleavage are evidenced by a positive shift in the reduction of acetochlor as compared to the more inert glassy carbon electrode. Voltammograms in the presence of 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP), and comparisons of calculated relative interaction energies between acetochlor, possible intermediates, and deschloroacetochlor in the presence of different proton donors, suggest strong hydrogen-bonding interactions between HFIP and a carbanion intermediate. Addition of HFIP to electrolysis conditions promotes complete reduction at both cathode materials, with formation of deschloroacetochlor in high yields. In deuterium labelling studies, the use of DMF- d 7 led to no evidence for deuterium atom incorporation. However, when HFIP-OD or D2 O were employed as a proton source, substantial amounts of deuterated deschloroacetochlor were observed. A mechanism for the reduction of acetochlor is proposed, in which radical intermediates do not play a significant role in reduction, rather a carbanion intermediate pathway is followed.